2019
DOI: 10.1111/jpy.12860
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the Linnaean Ulva lactuca (Ulvales, Chlorophyta) holotype and related type specimens reveals name misapplications, unexpected origins, and new synonymies

Abstract: Current usage of the name Ulva lactuca, the generitype of Ulva, remains uncertain. Genetic analyses were performed on the U. lactuca Linnaean holotype, the U. fasciata epitype, the U. fenestrata holotype, the U. lobata lectotype, and the U. stipitata lectotype. The U. lactuca holotype is nearly identical in rbcL sequence to the epitype of U. fasciata, a warm temperate to tropical species, rather than the cold temperate species to which the name U. lactuca has generally been applied. We hypothesize that the hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 27 publications
(45 reference statements)
4
80
0
10
Order By: Relevance
“…U. lactuca was described on the basis of the epitype of U. fasciata (UC2050475) that supports the lectotype (PC0119343) from New Port, Alexandria, Egypt by Delile including the holotype of U. fenestrata from Kamchatka, Russia by Postels and Ruprech (Hughey et al 2019). Although it is one of the most cosmopolitan species found in all temperature conditions (Hughey et al 2019), the true taxonomic position of U. lactuca was only recently revealed through advanced analysis of the lectotype specimen for variations of tufA and rbcL. That analysis indicated that the type specimen of U. fasciata Delile first reported from Alexandria, Egypt and specimens recognized as U. fasciata collected worldwide are all U. lactuca, while numerous specimens recognized to date in width ( Fig.…”
Section: Ulva Lactuca Linnaeus 1753 P 1163 (Fig 4a-c and E-g)mentioning
confidence: 86%
See 2 more Smart Citations
“…U. lactuca was described on the basis of the epitype of U. fasciata (UC2050475) that supports the lectotype (PC0119343) from New Port, Alexandria, Egypt by Delile including the holotype of U. fenestrata from Kamchatka, Russia by Postels and Ruprech (Hughey et al 2019). Although it is one of the most cosmopolitan species found in all temperature conditions (Hughey et al 2019), the true taxonomic position of U. lactuca was only recently revealed through advanced analysis of the lectotype specimen for variations of tufA and rbcL. That analysis indicated that the type specimen of U. fasciata Delile first reported from Alexandria, Egypt and specimens recognized as U. fasciata collected worldwide are all U. lactuca, while numerous specimens recognized to date in width ( Fig.…”
Section: Ulva Lactuca Linnaeus 1753 P 1163 (Fig 4a-c and E-g)mentioning
confidence: 86%
“…S1). On the other hand, U. ohnoi was composed of the center (n = 41) from two (Hughey et al 2019). In the Ulva bloom areas of Jeju, this species is always the predominant species in conjunction with U. ohnoi, U. australis, U. laetevirens, and U. pseudo-ohnoi sp.…”
Section: Ulva Pseudo-ohnoimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we apply optotracing as a novel method for carbohydrate analysis with the aim to shed new light on the carbohydrate composition of the extracted cellulose and the produced CNF. Even though Hughey et al (2019) suggested that the oldest available name for the northern hemisphere 'Ulva lactuca' is Ulva fenestrata, we will refer to the species used in our study as Ulva lactuca for reasons of general understanding. In the cellulose extraction process, we will try to replace sodium hypochlorite and methanol with hydrogen peroxide and ethanol in an attempt to apply greener extraction conditions than those reported in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the summer, the crusts were overgrown by the red and green algae Cystoclonium purpureum , Ceramium virgatum , and Ulva fenestrata (cf Hughey et al. ) and difficult to spot. Crusts were up to 7 cm in diameter.…”
Section: Resultsmentioning
confidence: 99%